The Effect of Halal Awareness and Halal Certification on Interest in Buying Halal Products During Covid-19 Pandemic - Yeyen Novita; Arna Asna Annisa; Anton Bawono; Ahmad Ulil Albab Al Umar; Adellia Kusuma Rachmawati; Nailis Safaah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of halal awareness and halal certification on interest in buying halal products during the Covid-19 pandemic. This study used quantitative methods to collect data as many as 138 respondents. The results of this study were analyzed through validity, reliability, R square, T test and F test using SPSS version 22 as an analytical tool. Based on the test results, the results showed: halal awareness had a significant positive effect on buying interest in halal products. Halal certification has a significant positive effect on interest in buying halal products. The implications of this research are expected as a reference in order to measure the extent to which the object of this research is to increase awareness about halal products and knowledge of the use of halal certification in the products to be purchased